Subaltern climate change adaptation : a framework on strategic resilience in subnational border communities, Ilocos Norte, Philippines - Dascil, Rommel Meneses (Divine Word College of Laoag : [s.n.], 2020)
Framed along pluralist and critical social theories, the study offers an innovative climate adaptation epistemological construct-subaltern adaptation -which necessitates the reimagining of the 'community' as a spatio-temporal ('historical' space) and spatio-social ('anthropological' space) within a particular ecological zone, instead of the usual state-centric scale (e.g, the barangay as community), as a new and ideal site for climate change adaptation analysis and methodology. With the border- community as point of departure, it takes the subnational border- community as locus, and the local institution as unit of analysis, upon which it offers a subaltern climate change adaptation framework on strategic community-level resilience. Grounded on the assumption that adaptation is a function and fusion of institutional strategy, inter-institutional partnership, and linked ecological and demographic realities, the study aims to propose a framework that fashions the complex and fundamental relationship between climate change, environment, and society, as lens to reveal the socio-ecological realities and vulnerability issues shared by local institutions in the border- community, and offers a methodical strategy that can guide interinstitutional, transborder or cross-scalar adaptation towards the creation of a resilient subaltern climate change community. Conducted in the Philippines in 2020, this research and development study maps the local institutions (civic, private, public) and their typologies in three border-communities situated in different ecological zones (upland, lowland, coastal), viability of inter-institutional transborder adaptation, institutional memory on climate-induced hazards and their impacts, and the local institution's perception on future hazards as well as their recommended action. Generally, the findings reveal that the local institutions adaptive capacity is promising and can be enhanced through inter-institutional transborder collaboration, which almost all are willing to venture into. Such transborder collaboration is basically geared at addressing the geospatial and social vulnerabilities that the local institutions share across the border, which ultimately addresses the C constraints that state-defined borders have on the border-community. Subjected to the rigid evaluation of validators, who are engaged in community and rural development, climate change and sustainable development, governance, and social action, the framework proposed by this study is adjudicated as valid and implementable. The study recommends the necessary and diversity-sensitive adoption of the framework by the local institutions in the border-community, and the support of state and NGOs to allow bottom-up and horizontal adaptation strategy facilitated and mediated by local institutions across borders, even as it encourages future researchers to bravely dwell into frontier knowledge production on climate change adaptation and propose new pathways towards lasting community-driven and -managed climate change resilience.
Bibliography: pages 307-329.
CHED-La Union
Keywords: Climate change -- Ilocos Norte